Message from Mr Tewson regarding Mr Ballajan - Kennard, Ethel K.
C02-0070-001 9th May, 1938. 2.20 p.m. Message from Mr. Tewson, given to me by Miss Cobbett :- MRS. BALLAJAN. 3056 Bayswater. Mr. Tewson has spoken to the wife of the Spanish Ambassador in Paris, I understand, and this man, Mr. Ballajan, is connected with the Embassy, and wants to know whether he can buy Medical Goods for Spain, and is hoping they will be able to get some money. Mr. Tewson thinks that as Dr. Morgan is connected with the Spanish Medical Aid Committee it would be better for Dr. Morgan to have a word with Mr. Ballajan on the 'phone. EKK. 292C/946/2/70